Strategi pengambangan bisnis dengan menggunakan metode Business Model Canvas pada UMKM TLC karawang - Ashomaji Destiana Refdy; Endah Purwanti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The increasing growth of restaurants will create increasingly fierce competition in the culinary industry at this time. Business owners in the culinary industry are required to be able to innovate and use competitive strategies that are in accordance with the development of their business environment conditions to be able to further develop for the better. The research aims to identify, and analyze the Business Model Canvas in TLC. The data collection method used is descriptive qualitative. After identifying the Business Model Canvas, an analysis will be carried out on each element consisting of key partnerships, customer relationships, customer segments, channels, value propositions, key activities, cost structures, revenue streams and key resources, and Analyzed with a SWOT analysis. The results of the Business Model Canvas analysis, there are several elements in the business model that can be developed again with the aim of increasing revenue.